Frontline Science: A hyporesponsive subset of rat NK cells negative for Ly49s3 and NKR‐P1B are precursors to the functionally mature NKR‐P1B+ subset. Issue 6 (26th July 2017) - Sudworth, Amanda; Vaage, John T.; Inngjerdingen, Marit; Kveberg, Lise
Abstract : Functional competence of hyporesponsive rat NK cells is associated with acquisition of the inhibitory receptor NKR‐P1B. Abstract : Rat NK cells are divided into major subsets expressing either Ly49 receptors or the inhibitory NKR‐P1B receptor in conjunction with NKG2A/C/E receptors. A minor subset of NKp46 + cells lacking expression of both Ly49 receptors and NKR‐P1B is present in blood and spleen and is associated with decreased functional competence. We hypothesized that this subset may represent precursors to Ly49 + and/or NKR‐P1B + NK cells. When cultured in vitro in IL‐2 and IL‐15 or adoptively transferred to syngeneic hosts, a portion of NKR‐P1B − Ly49s3 − cells transformed to express NKR‐P1B, but very little Ly49s3. Acquisition of NKR‐P1B by NKR‐P1B − Ly49s3 − cells coincided with increased degranulation. In addition, although NKR‐P1B − Ly49s3 − cells highly proliferate, proliferative activity was reduced upon acquisition of NKR‐P1B at comparable levels to bona fide NKR‐P1B + NK cells. A fraction of NKR‐P1B − Ly49s3 − cells remained negative for NKR‐P1B, both in vitro and after adoptive transfer in vivo. Most NKR‐P1B − Ly49s3 − cells expressed the transcription factor Eomesodermin and NK cell markers, indicating that these cells represent conventional NK cells. Our findings suggest that the NKR‐P1B − Ly49s3 − NK cells are precursors to NKR‐P1B single‐positive cells and that functional competence is acquired upon expression of NKR‐P1B.